Comparative Analysis Of Conventional Banks Financial Performance Before And During The Covid-19 Pandemic: Case Study At Registered Conventional Banks On The Indonesia Stock Exchange In The Period Of 2018 – 2021 - Sari, Ervina Indri; Lestary, Fellya Destriliawaty Indah; Nurjanah, Yayuk (Institut Bisnis dan Informatika Kesatuan, 2025)
The Covid-19 pandemic has had a significant impact on the banking sector, especially conventional banks. This study analyzes the comparison of the financial performance of conventional banks before and during the COVID-19 pandemic in the 2018–2021 period. The type of research used in this study is comparative research with a quantitative research method approach, with the Purposive Sampling sampling technique obtained a sample of 40 conventional banks in the 2018-2021 period. This study uses the CAMEL method to assess the financial health of banks based on the Capital Adequacy Ratio (CAR)), Asset Aspect (Productive Asset Quality (KAP)), Management Aspect (Net Interest Margin (NIM)), Earning Aspect (Return On Assets (ROA) & Operating Costs to Operating Income (BOPO)), and Liquidity Aspect (Loan to Deposit Ratio (LDR)). Data was obtained from financial statements that had been audited and analyzed using the paired t-test and the Wilcoxon signed-rank test. The results showed that there were significant differences in CAR, NIM, ROA, BOPO, and LDR before and during the pandemic, indicating changes in banks' risk management strategies, profitability, and efficiency in the face of crises. However, asset quality (KAP) did not show a significant difference, indicating that banks are still able to maintain stability in credit returns despite economic disruptions. This study has limitations on the scope of the sample which only includes banks listed on the stock exchange and does not consider external factors outside the financial sector. The results of this study provide insight into the resilience of conventional banks in facing economic crises and become a reference for policymakers and financial institutions in strengthening banking stability in the future. Keywords: Financial Performance, CAMEL Method, Covid-19